Insight into the avidity–affinity relationship of the bivalent, pH-dependent interaction between IgG and FcRn - Johannes Reusch; Jan Terje Andersen; Ulrich Rant; Tilman Schlothauer (mAbs, 2024)
Monoclonal antibodies (mAbs) as therapeutics necessitate favorable pharmacokinetic properties, including extended serum half-life, achieved through pH-dependent binding to the neonatal Fc receptor (FcRn). While prior research has mainly investigated IgG-FcRn binding kinetics with a focus on single affinity values, it has been shown that each IgG molecule can engage two FcRn molecules throughout an endosomal pH gradient. As such, we present here a more comprehensive analysis of these interactions with an emphasis on both affinity and avidity by taking advantage of switchSENSE technology, a surface-based biosensor where recombinant FcRn was immobilized via short DNA nanolevers, mimicking the membranous orientation of the receptor. The results revealed insight into the avidity-to-affinity relationship, where assessing binding through a pH gradient ranging from pH 5.8 to 7.4 showed that the half-life extended IgG1-YTE has an affinity inflection point at pH 7.2, reflecting its engineering for improved FcRn binding compared with the wild-type counterpart. Furthermore, IgG1-YTE displayed a pH switch for the avidity enhancement factor at pH 6.2, reflecting strong receptor binding to both sides of the YTE-containing Fc, while avidity was abolished at pH 7.4. When compared with classical surface plasmon resonance (SPR) technology and complementary methods, the use of switchSENSE demonstrated superior capabilities in differentiating affinity from avidity within a single measurement. Thus, the methodology provides reliable kinetic rate parameters for both binding modes and their direct relationship as a function of pH. Also, it deciphers the potential effect of the variable Fab arms on FcRn binding, in which SPR has limitations. Our study offers guidance for how FcRn binding properties can be studied for IgG engineering strategies.